(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study examines the impact of hotel reservation systems—both own and third-party on guest satisfaction in Delhi hotels. Utilizing a descriptive survey methodology, structured questionnaires were administered to 302 guests from 32 Ministry of Tourism-approved hotels in Delhi. Among these, 216 guests used third-party reservation systems, while 86 utilized hotel-owned systems. On a 5-point Likert scale, guests rated 20 service attributes, ranging from entirely satisfied to very dissatisfied. In order to identify the broad factors of customer satisfaction, principal component analysis with Varimax rotation was implemented. Subsequently, multiple regression analysis was implemented to evaluate the contribution of all factors to guest’s satisfaction. The findings underscore the importance of reservation systems in shaping guest experiences in Delhi hotels. While both third-party and hotel-owned systems contribute positively to guest satisfaction, their impacts vary across different dimensions of service delivery.